Risk management in a small family-owned nursery: A case study approach. Issue 1 (2nd January 2022) - Mitter, Christine; Kuttner, Michael; Berchtenbreiter, Andreas
ABSTRACT: Our study is among the first dealing with risk management in small family businesses and contributing to the understanding of family businesses in the context of risk management. Results stem from a conclusive data triangulation of primary (interviews and perceptions from several company visits) and secondary data (for example, analysis of the corporate website and additional company data) of a small family-owned nursery and are discussed under aspects of stewardship theory, which has three forms of expression (stewardship over continuity, employees, and customers) in family businesses. In detail, we illustrate how risks could be managed and risk management could be designed in a small family business. Furthermore, we point out the central role of the owner-manager and the corporate family in risk management. Results also highlight the relevance of informal and less-formalized risk management, which has been largely neglected so far within accounting literature.